2015
DOI: 10.5539/elt.v8n2p153
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Listening Strategies Used by Egyptian EFL College Sophomores and Their Listening Comprehension and Self-Efficacy

Abstract: The present study explored listening strategy use among a group of Egyptian EFL college sophomores (N = 84). More specifically, it aimed to identify 1) the strategies used more often by participants, 2) the relationship between listening strategy use, and listening comprehension and self-efficacy, and 3) differences in listening comprehension and self-efficacy between students with high and low strategy frequency. A Listening Comprehension Test adapted from paper-based Longman TOEFL test was used to assess par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 45 publications
6
48
0
2
Order By: Relevance
“…Many teachers or researchers start focusing their concerns on the development of students' learning strategies (Khamdani, 2014;Basir, 2014;Kassem, 2015). This circumstance is seen as the impact of previous influential research that had been done by some experts (Rubin, 1987;Cohen, 1998;O'Malley et al, 1985;Oxford, 1990;Stern, 1992;etc).…”
mentioning
confidence: 99%
“…Many teachers or researchers start focusing their concerns on the development of students' learning strategies (Khamdani, 2014;Basir, 2014;Kassem, 2015). This circumstance is seen as the impact of previous influential research that had been done by some experts (Rubin, 1987;Cohen, 1998;O'Malley et al, 1985;Oxford, 1990;Stern, 1992;etc).…”
mentioning
confidence: 99%
“…19)." Kassem (2015) has reported that efficient listeners effectively use LCS to comprehend the target listening texts better. He has further stated that LCS "if identified and described, can be taught to less successful learners to better their learning" and a growing mass of research of this type has developed "several, but similar taxonomies of listening strategies" (p. 156).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much research has been conducted to identify and classify LCS exploited by EFL/ESL learners (see for example Vandergrift, 2003;Liu, 2008;Serri, Boroujeni, & Hesabi, 2012;Nowrouzi, Tam, Nimehchisalem, & Zareian, 2014). Several other studies have investigated the comparative analyses of LCS used by more proficient and less proficient language learners (see for example Staehr, 2008;Milton, Wade, & Hopkins, 2010;Bidabadi & Yamat, 2011;Tavakoli, Shahraki, & Rezazadeh, 2012;Kassem, 2015). It has been reported that a growing mass of research has investigated the use of LCS in relation to variables like listening comprehension, self-efficacy and anxiety (Chen, 2007;Liu, 2008;Lu, & Liu, 2011;Golchi, 2012;Ghapanchi, & Golparvar, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations